Prospective study of the ankle inversion destabilization maneuver for acute ankle ligament injury - Antonio de Oliveira Galati, Danilo; Carillo Ambrosio, Gustavo Henrique; Szejnfeld Mann, Tania; Pochini, Alberto de Castro; Salomao Barbachan Mansur, Nacime (Journal of the Foot & Ankle, 2024)
Objective: Present the result of a new maneuver for treating lateral ankle sprains. Methods: A new technique for sensorimotor stimulation was incorporated into the conventional rehabilitation process of 100 patients with acute lateral ankle sprain with a 12-month follow-up. The primary outcome was new sprain episodes, and the secondary outcomes included quality of life (assessed by the Health Survey 12 questionnaire (SF-12)), pain (assessed by the Visual Analog Pain Scale (VAS)) function (assessed by the American Orthopaedics Foot & Ankle Society - Ankle-Hindfoot Scale - (AOFAS)) and patient-reported instability symptoms (assessed by the Cumberland Ankle Instability Tool (CAIT)). Results: Among the patients included, a 12-month recurrence rate of new sprain episodes was observed at 6% (95%CI: 4.7%), which is statistically significant compared to the data reported in the literature. Regarding secondary outcomes, a statistically significant difference was observed among the onset, eight weeks, and 12 months in the AOFAS and CAIT scores. A statistically significant difference in the periods was also observed in VAS, with an initial mean of 5.94 to 1.29 at the end of treatment. Conclusion: Based on our findings, a 12-month follow-up, the ankle inversion destabilization maneuver added to a standard rehabilitation protocol proved effective in preventing new lateral ankle sprain episodes. Level of evidence IV; Case series; Therapeutic studies - investigating the results of treatment